2 - The ICC, International Criminal Justice and International Politics - Mensa-Bonsu, Henrietta J.A.N. (Africa Development, 2021)
The International Criminal Court (ICC) came into being as a result of a desire by the international community to establish a permanent body to deliver criminal justice instead of the formula of ad hoc tribunals that had become the norm. The coming into force of the Rome Statute in 2002 was greeted with euphoria as it signified to many that a new era had dawned when the international community would, with one voice, say no to impunity and create a deterrent effect to crimes of genocide, crimes against humanity, war crimes and crimes of aggression. The slowness with which the court has moved in concluding cases, as well as its perceived lack of even-handedness in selecting what cases to pursue, have resulted in widespread disappointment and disaffection, even to the extent of generating hostility in some of its former supporters. Has the ICC indeed failed to live up to expectations, or were those of its proponents unrealistic, and the criticism of its detractors unfair? Are the ICC’s weaknesses a function of its very nature or externally-imposed by the machinations of international politics? Is there a need for the world in general, and Africans in particular, to look beyond the ICC for protection from their own people, and for ending impunity in a decisive manner? In short, does it have a future, and how shall it remain relevant in the future? This article is a think piece on the ICC, its failings, perceived or real, and its prospects for achieving what it was originally conceived to be and to become in the world of international criminal justice.